Surface study of doped and coated Li-rich Mnbased cathode materials and their interactions with the electrolyte content - Ramogayana, Brian (My University, 2024)
Since its introduction, lithium manganese-based lithium-ion batteries have advanced in terms of safety, capacity, power, cycle stability, and energy density. These have been attributed to the use of innovative and customised active (cathode) materials with increased capacity, potential, and thermal stability. Furthermore, given the high global manganese output and the present load-shedding situation, South Africa stands to gain considerably. However, modern Li-ion batteries must be replaced over time owing to deterioration caused by cathode interactions with the electrolyte, which causes capacity fading. As a result, modifications such as surface coating and element doping are used to enhance and minimize deterioration processes. The density functional theory technique was used in this work to investigate the effect of surface Nb-doping and α-Al2O3 surface coating on the LiMn2O4 major surfaces. First, the bulk characteristics of both LiMn2O4 and α-Al2O3 were studied, as well as the stability and precision of our materials in comparison to reference data. The estimated lattice characteristics, average atomic charges, and bond distances matched the provided values. With Mn eg and O 2p hybridization along the Fermi level, the electronic density of states of LiMn2O4 bulk displayed a half-metallic behaviour. Similarly, the α-Al2O3 exhibited insulating behaviour with a large band gap of 5.90 eV, which was consistent with the literature results. Second, the ethylene carbonate electrolyte (EC) interactions with the α-Al2O3 (0001) surface were investigated, even with increasing EC coverage. When put parallel (flat) to the surface and interacting with the carbonyl oxygen, the EC molecule favoured attaching to the surface. A minor charge transfer was found during single EC adsorption, suggesting physical interactions with the surface. When compared to single EC adsorption, increasing the EC coverage destabilizes the surface and increases average adsorption. Bader charge accumulation was seen on the interacting EC oxygen atoms, with substantial steric hindrance at high coverages, resulting in the EC molecule detaching from the surface. Steric hindrance was also shown by the symmetric and asymmetric blue shift of v(CH2) vibrational modes. Furthermore, we created 𝛼-Al2O3//LiMn2O4 heterostructures to simulate the 𝛼-Al2O3 coated LiMn2O4 surfaces. We discovered that the 𝛼-Al2O3 (112 ̅0) and (0001) surfaces match the LiMn2O4 (001) and (111) facets with {1132} and {3121} configurations, respectively, with 2.40% and 2.75% misfits. The highest adhesion energies were determined for the 𝛼-Al2O3 monolayer on the (001) and (111) surfaces, which dropped as the thickness increased. A minor average charge transfer on the LiMn2O4 substrate surfaces was computed, and charge depletion on the interacting Mn atoms creating MnO6 units at the heterojunction was observed. Following partial delithiation, the vacancy formation energies rise, prompting minor charge depletion on neighbouring Mn atoms in the form of charge redistribution. When compared to pure surfaces, the computed work function rises, indicating that the coated interfaces become less reactive. Finally, surface Nb doping was studied on the LiMn2O4 (001), (011), and (111) surfaces. It was discovered that substituting Nb at Mn ion locations in the second surface layers (Nbsecond) increased (111) surface stability, forming a larger (111) facet on the morphology. However, Nbdoping on the top (Nbfirst) and both top and bottom (Nbboth) surface layers results in the same stability as clean surfaces. Furthermore, we examined EC and HF adsorption on pristine/Nb doped surfaces, and both adsorbates favoured interactions with the facets via Nb atoms over Mn atoms. A higher binding energy was calculated for EC on Nbsecond (011) surface and HF on Nbboth (111) surface. EC Adsorption results in physical interactions with surfaces, whereas HF decomposes into H and F atoms that adhere to surface O and Mn atoms, respectively and both improve the Nbsecond (111) surface stability. A minimal charge transfer was observed upon HF and EC interacted with pure or Nb-doped surfaces. These findings are noteworthy because improving the (111) surface on the morphologies could promotes the formation of a stable solid electrolyte interface (SEI), which reduces dissolution of Mn while enhancing EC and HF adsorption.
Thesis (Ph.D. (Physics)) -- University of Limpopo, 2024
Keywords: Lithium ion batteries; Semi conductors; Electrolyte content; Doped semiconductor superlattices; Lithium ion batteries; Electrolytes